2020
DOI: 10.2147/dmso.s254555
|View full text |Cite
|
Sign up to set email alerts
|

<p>Therapeutic Effects of Garlic on Hepatic Steatosis in Nonalcoholic Fatty Liver Disease Patients: A Randomized Clinical Trial</p>

Abstract: Background and Aims: Emerging evidence suggests that garlic (Allium sativum L.) and its bioactive components can mitigate hepatic steatosis by the modulation of hepatic lipid metabolism. We aimed to assess the efficacy of the garlic administration on hepatic steatosis in patients with NAFLD. Patients and Methods: This clinical trial was conducted on adult patients with ultrasounddiagnosed NAFLD. Eligible participants were randomly assigned, with the use of the stratified blocked procedure, to receive 800 mg ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 37 publications
1
30
0
Order By: Relevance
“…Moreover, an 8-week single-arm trial on 36 NAFLD patients showed that the consumption of the curcumin-phospholipid complex at a dose of 1,500 mg per day could ameliorate NAFLD severity and none of the severe adverse events were reported [ 190 ]. Besides, a clinical trial based on 98 NAFLD patients showed that the intake of 800 mg garlic for 15 weeks could improve hepatic steatosis compared with the placebo group (RR: 5.6; 95%CI: 2.17, 14.5) with no serious adverse effects [ 191 ]. Allicin is a common phytochemical from garlic, and a previous high-quality article summarized the safety assessment of allicin application and emphasized that the high-dose consumption of allicin (30 to 59 mg) could cause stomach irritation, especially when people were in a fasting state or ingested too fast [ 192 ].…”
Section: Safety and Application Issues Of Plant-based Foods And Thmentioning
confidence: 99%
“…Moreover, an 8-week single-arm trial on 36 NAFLD patients showed that the consumption of the curcumin-phospholipid complex at a dose of 1,500 mg per day could ameliorate NAFLD severity and none of the severe adverse events were reported [ 190 ]. Besides, a clinical trial based on 98 NAFLD patients showed that the intake of 800 mg garlic for 15 weeks could improve hepatic steatosis compared with the placebo group (RR: 5.6; 95%CI: 2.17, 14.5) with no serious adverse effects [ 191 ]. Allicin is a common phytochemical from garlic, and a previous high-quality article summarized the safety assessment of allicin application and emphasized that the high-dose consumption of allicin (30 to 59 mg) could cause stomach irritation, especially when people were in a fasting state or ingested too fast [ 192 ].…”
Section: Safety and Application Issues Of Plant-based Foods And Thmentioning
confidence: 99%
“…Garlic as a prebiotic increases the growth and activity of health‐promoting bacteria in the gut (Filocamo, Nueno‐Palop, Bisignano, Mandalari, & Narbad, 2012; Ried, Travica, & Sali, 2018). Furthermore, garlic improves inflammation, dyslipidemia, obesity, insulin concentrations, and hepatic steatosis (Chen et al, 2019; Maeda et al, 2019; Ried, Travica, & Sali, 2016; Soleimani, Paknahad, & Rouhani, 2020; Trio et al, 2014). In addition to lifestyle modification (adherence to healthy diets, weight loss, and physical activity) as the main strategy in the management of NAFLD (Zelber‐Sagi, Godos, & Salomone, 2016), prebiotics can stimulate satiety hormones and decrease food intake, and reduce body fat accumulation as well as hepatic steatosis (Hume, Nicolucci, & Reimer, 2017; Parnell & Reimer, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, this goal is not feasible and poses a major challenge for many patients (Vilar‐Gomez et al, 2015). Emerging evidence suggested the use of some of the functional foods and nutriceuticals as potential therapeutic agents for NAFLD because of their potential to interfere with signaling pathways in NAFLD pathogenesis (Cicero, Colletti, & Bellentani, 2018; Mahmoodi et al, 2020; Najafpour Boushehri et al, 2020; Soleimani, Paknahad, & Rouhani, 2020).…”
Section: Introductionmentioning
confidence: 99%